The cytoarchitonics, the intrinsic organization and the afferent termination patterns of the Globus pallidus: A light and electron microscopic study. - Lu Qui, Ivan James. (University of Ottawa (Canada), 1968)
Abstract not available.
Keywords: Biology, Anatomy.